The effectiveness of a co-management care model on older hip fracture patients in China - A multicentre non-randomised controlled study - Jing Zhang; Minghui Yang; Xinyi Zhang; Jiusheng He; Liangyuan Wen; Xianhai Wang; Zongxin Shi; Sanbao Hu; Fengpo Sun; Zishun Gong; Mingyao Sun; Qiang Li; et al. (Elsevier, 2022)
Summary: Background: Clinical guidelines recommend orthogeriatric care to improve older hip fracture patients' outcomes, but few studies have been conducted in China. This study evaluated the effects of an orthogeriatric co-management care model in six Chinese hospitals. Methods: This non-randomised controlled study was designed as an exploratory trial and was conducted in 3 urban and 3 suburban hospitals. Eligible patients were aged ≥ 65 years with X-ray confirmed hip fracture and admitted to hospital within 21 days of injury. All patients received three times follow-ups within one year (1-month, 4-month and 12-month post admission). Co-management care was implemented in 1 urban hospital, while usual care continued in 5 urban and suburban hospitals. Patient demographics, pre-, peri- and post-operative information, complications and mortality were collected at baseline and follow-ups. The primary outcome was proportion of patients receiving surgery within 48 hours from ward arrival. Secondary outcomes included osteoporosis assessment, in-hospital rehabilitation, length of hospital stay, in-hospital mortality and one-year cumulative mortality. Findings: There were 2,071 eligible patients enrolled (1,110 intervention, 961 control). Compared to usual care, a significantly higher proportion of intervention patients received surgery within 48 hours (75% vs 27%, p<0.0001), osteoporosis assessment (99.9% vs 60.6%, p<0.0001), rehabilitation (99.1% vs 3.9%, p<0.0001) and shorter length of hospital stay (6.1 days vs 12.0 days, p<0.0001). The intervention group saw a significant lower in-hospital mortality rate than the control group (adjusted relative risk 0.021, 95% CI 0.001 to 0.45, P=0.01). One-year cumulative mortality was also significantly reduced in the intervention group (hazard ratio 0.59, 95% CI 0.38 to 0.80, p=0.01). Interpretation: Co-management care of older hip fracture patients resulted in better outcomes, including decreased time to surgery, improved clinical management, and reduced one-year mortality. A randomised controlled trial is needed to provide definitive evidence. Funding: The study is supported by Capital's Funds for Health Improvement and Research (2018-1-2071).